HIGHLY SELECTIVE LOSSY DUAL-BAND BANDSTOP FILTER REALIZATION BASED ON PREDISTORTION HYBRID REFLECTION FUNCTIONS - SOCHEATRA, SOEUNG (2018)
Filters are one of the most important parts in communications systems to filter or suppress any unwanted signals at both transmitter and receiver sides to avoid any possible radiation of signals into main frequency spectra. They can adapt to various topologies depending upon the requirements.